SEX EDUCATION AS A FOUNDATION OF CHRISTIAN FAITH TO THE HOLY DOCTRINES - David Ming (Inculco Journal of Christian Education, 2021)
Abstract: Today's world continues to change, including the way people perceive sex problems. Some of the problems that arise are: What is meant by education? Sex in a world of sin? How is the Relationship of Sex Education as a Foundation of Christian Faith to the Doctrine of Holiness according to Reformed? The answer: (1) The Bible's view of sex education is God's work on humans since creation. (2) Sex is something sacred as God instituted marriage for the first time in Eden. (3) Sex education can be related to the doctrine of holiness as the foundation of Christian faith as follows: First, it is necessary to develop holiness education in schools, seminars and in churches in order to clarify the position of sexual sinfulness committed outside of marriage. Second, God-centered holiness becomes dependent only on God and not on humans. Third, the holiness modeled by Jesus becomes a figure that everyone can imitate so that everyone has a calling to live.Abstrak: Dunia sekarang ini terus mengalami perubahan termasuk pandangan orang terhadap masalah seks. Beberapa persoalan yang muncul adalah: Apakah yang dimaksud dengan pendidikan? Seks dalam dunia keberdosaan? Bagaimanakah Relasi Pendidikan Seks sebagai Landasan Iman Kristen terhadap Doktrin Kekudusan menurut Reformed? Jawabnya: (1) Pandangan Alkitab tentang pendidikan  seks adalah merupakan karya Allah pada diri manusia sejak diciptakan. (2) Seks adalah sesuatu yang sakral sebagaiman Allah melembagakan pernikahan pertama kali di Eden. (3) Pendidikan seks dapat direlasikan dengan doktrin kekudusan  sebagai landasan iman Kristen sebagai beriku: Pertama, perlunya dikembangkan pendidikan kekudusan di sekolah-sekolah, seminar maupun di gereja agar memperjelas posisi keberdosaan seks yang dilakukan di luar pernikahan. Kedua,  kekudusan yang berpusat kepada Allah menjadi ketergantungan hanya kepada Allah bukan kepada manusia. Ketiga, kekudusan yang diteladani oleh Yesus menjadi tokoh yang dapat diteladani  oleh semua orang sehingga setiap orang mempunyai panggilan untuk hidup